Working with lunar surface materials: Review and analysis of dust mitigation and regolith conveyance technologies. (July 2022) - Cannon, Kevin M.; Dreyer, Christopher B.; Sowers, George F.; Schmit, John; Nguyen, Thao; Sanny, Keoni; Schertz, Joshua
Abstract: The Moon's dusty surface environment threatens any equipment that operates there, especially for long-duration infrastructure needed for a sustained lunar presence. This is doubly true for systems that convey regolith, which by agitating the soil are certain to generate dust. Here, we provide a comprehensive review of technologies that have been proposed to convey regolith on the lunar surface, and to mitigate against dust hazards that are generated by such transport systems. We define functional taxonomies for both regolith conveyance and dust mitigation, then carry out quantitative trade studies in several categories for each. Examples include passive and active dust mitigation, and horizontal and near vertical conveyance. Conveyance technologies that scored particularly high include wheeled haulers, conveyor belts, and auger/hopper transfer points. High scoring dust mitigation technologies include the lotus leaf passive coating, Electrodynamic Dust Shield, and boots or bellow made of fiberglass fabric. We also explore novel or unconventional concepts and describe how dust mitigation and regolith conveyance can be combined using a systems approach with multiple technologies layered together. The results from the trade studies and the subsequent recommendations constitute a practical guide that can be used for designing and developing systems that must perform efficiently and reliably to carry out useful tasks on the Moon or Mars, such as resource extraction, construction, and additive manufacturing. Highlights: New taxonomies defined for dust mitigation and regolith conveyance technologies. Quantitative engineering trade studies used to compare between techniques. For dust, lotus coatings, EDS, and fiberglass fabric scored highest. For conveyance, wheeled haulers, conveyor belts, and auger/hoppers scored highest.